An Adolescent with Hyperimmunoglobulinemia D and Periodic Fever Syndrome Responding to Simvastatin Treatment - Elif KARAKOÇ-AYDINER; Cevdet ÖZDEMİR and Sevgi KELEŞ and Safa BARIŞ and Nerin N. BAHÇECİLER and Işıl B. BARLAN (Archives of Rheumatology, 2011)
The hyperimmunoglobulinemia D and periodic fever syndrome is proposed to be caused by a defect in the activity of mevalonate kinase enzyme which is involved in cholesterol and non-sterol isoprenoid biosynthesis. This autosomal recessive inherited autoinflammatory syndrome is characterized by recurrent fever attacks, abdominal pain, lymphadenopathy, skin lesions and joint involvement. In this article, we present our therapeutic approach with the hypolipidemic agent, simvastatin, in a 12-year-old boy followed up with a diagnosis of hyperimmunoglobulinemia D and periodic fever syndrome. Simvastatin treatment of an adolescent with hyperimmunoglobulinemia D and periodic fever syndrome unresponsive to anti-inflammatory strategies has resulted in a favorable outcome. This treatment is thought to reduce the recurrent fever attacks by reducing the mevalonic acid increase or isopreniod shortage.